Validitas Perangkat Pembelajaran IPA Model Inkuiri Terbimbing untuk Melatihkan Keterampilan Pemecahan Masalah Siswa SMP Materi Pencemaran Lingkungan - Rusmi Indriyani; Joko Waluyo; Jekti Prihatin (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
This research is aimed to produce science learning equipments of guided inquiry model for training student problem solving skill in environment pollution materials and to describe the validity base on validaty of by an educational expert, an material expert, and science teacher using validation of sheet. This research uses four-D model that consists of define, design, develop, and disseminate step. The result of this research are syllabus, lesson plane, student books, student work sheet, student tests. The average of validaty lesson plan 3,5, student books get average 3,5, student work sheets get average 3,5, and student tests get average 3,6.